2020
DOI: 10.1016/j.pedneo.2020.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Septic arthritis in children: Updated epidemiologic, microbiologic, clinical and therapeutic correlations

Abstract: Background: Septic arthritis (SA) is an infection characterized by significant epidemiologic and microbiologic differences between developed and developing regions and between age groups. Objectives: To determine the epidemiologic, clinical, microbiologic and therapeutic aspects of pediatric SA in Southern Israel. Methods: A retrospective case-series study based on the records of children <16 years of age admitted with SA at Soroka Medical Center, Beer-Sheva, during 2006e2013. Results: 189 patients were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 22 publications
5
33
0
5
Order By: Relevance
“…The average length of hospital stay (LOS) (5.8 days) in our study is in agreement with US data [ 26 ], but is shorter than the reported 9.2 days in the Israeli study [ 10 ]. The rather short LOS is somewhat surprising but in keeping with recommendations that short intravenous antibiotic regimens followed by oral therapy are not inferior to long term intravenous therapy with regards to long-term outcomes [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The average length of hospital stay (LOS) (5.8 days) in our study is in agreement with US data [ 26 ], but is shorter than the reported 9.2 days in the Israeli study [ 10 ]. The rather short LOS is somewhat surprising but in keeping with recommendations that short intravenous antibiotic regimens followed by oral therapy are not inferior to long term intravenous therapy with regards to long-term outcomes [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…While a study from Norway reported an AIR of 5 per 100,000 based on 12 cases over a 1-year period, a recent long-term study based on the Kids’ Inpatients Database (KID) in the USA reported a stable AIR of 5.5 over two decades, which is in agreement with the AIR of 5.6 in non-Indigenous patients in WA. In contrast, the high AIR in Indigenous children (which make up approximately 6% of the total population aged < 16 years) support findings by Okuzo et al [ 11 ] and recent data from Israel [ 10 ] which demonstrated significantly higher rates in disadvantaged children and illustrate the importance of ethnicity and socioeconomic status in the incidence and hospitalization rates of SA. As in other studies, there was no large change in SA incidence over time [ 10 , 26 ], suggesting a limited effect of changes in medical practice, such as the increased use of immune suppression and invasive joint procedures for children [ 12 ].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations